Does advertisement call variation coincide with genetic variation in the genetically diverse frog taxon currently known as Leptodactylus fuscus (Amphibia: Leptodactylidae)? - HEYER,W. RONALD (2003)
The frog Leptodactylus fuscus is found throughout much of South America in open and disturbed habitats. Previous study of genetic differentiation in L. fuscus demonstrated that there was lack of genetic exchange among population units consistent with multiple species, rather than a single species. We examine advertisement vocalizations of L. fuscus to determine whether call variation coincides with genetic differentiation. Calls were analyzed for 32 individual frogs from 25 localities throughout the distributional range of L. fuscus. Although there is variation in calls among geographic samples, call variation is not concordant with genetic variation or geographic distance and the call variation observed is less than that typically found among other closely related species of Leptodactylus. This study is an example of the rare pattern of strong genetic differentiation unaccompanied by salient differences in advertisement calls. The relative infrequency of this pattern as currently understood may only reflect the lack of detailed analyses of genetic and acoustic differentiation within population systems currently understood as single species with substantial geographic distributions.